Identification des conditions favorables à un dialogue sur la gouvernance locale concertée des eaux souterraines - Hassenforder, Emeline (CGIAR FOCUS Climate Security, 2022)
All over the world, groundwater degradation and overexploitation are increasing. In semi-arid and arid areas such as the Maghreb, groundwater provides a significant share of water uses, and is therefore a major factor in the economy. With climate change, the development of irrigated agriculture and the growth of other water consuming sectors, pressures on groundwater resources are likely to increase. Yet current water policies struggle to curb these trends. In this context, a solution that is increasingly put forward is collaborative governance. But the specificities of groundwater ("invisibility", interdependencies between actors, less easily available data, etc.) complicate this collaborative governance. In Morocco, attempts to develop participatory groundwater contracts on large aquifers have been made for the past fifteen years, although not always living up to expectations (Del Vecchio, 2019). In Tunisia, a similar reflection is currently underway. In this activity, we argue that collaborative groundwater governance is not a panacea everywhere, and that a number of conditions must be met for this collaborative governance to be more effective and sustained over time. Through an analysis of cases and literature, we identified 15 conditions that are favorable to collaborative groundwater governance. These conditions are related to the resource itself (size of the aquifer, access to alternative water resources, etc.), to the actors and their interactions (territorial attachment, conflicts, etc.) and to institutional frameworks (resources available, respect of existing laws and management instruments, etc). These conditions have been tested in two aquifers in Tunisia. This synthesis presents our preliminary results.